Interference of Celastrol with Cell Wall Synthesis and Biofilm Formation in Staphylococcus epidermidis - Leandro de León Guerra; Nayely Padilla Montaño; Laila Moujir (Antibiotics)
Background: The emergence of antibiotic-resistant bacteria, including Staphylococcus epidermidis, underscores the need for novel antimicrobial agents. Celastrol, a natural compound derived from the plants of the Celastraceae family, has demonstrated promising antibacterial and antibiofilm properties against various pathogens. Objectives: This study aims to evaluate the antibacterial effects, mechanism of action, and antibiofilm activity of celastrol against S. epidermidis, an emerging opportunistic pathogen. Methods: To investigate the mechanism of action of celastrol, its antibacterial activity was evaluated by determining the time–kill curves, assessing macromolecular synthesis, and analysing its impact on the stability and functionality of the bacterial cell membrane. Additionally, its effect on biofilm formation and disruption was examined. Results: Celastrol exhibited significant antibacterial activity with a minimal inhibitory concentration (MIC) of 0.31 μg/mL and minimal bactericidal concentration (MBC) of 15 μg/mL, which is superior to conventional antibiotics used as control. Time–kill assays revealed a concentration-dependent bactericidal effect, with a shift from bacteriostatic activity at lower concentrations to bactericidal and lytic effect at higher concentrations. Celastrol inhibited cell wall biosynthesis by blocking the incorporation of N-acetylglucosamine (NAG) into peptidoglycan. In contrast, the cytoplasmic membrane was only affected at higher concentrations of the compound or after prolonged exposure times. Additionally, celastrol was able to disrupt biofilm formation at concentrations of 0.9 μg/mL and to eradicate pre-formed biofilms at 7.5 μg/mL in S. epidermidis. Conclusions: Celastrol exhibits significant antibacterial and antibiofilm activities against S. epidermidis, with a primary action on cell wall synthesis. Its efficacy in disrupting the formation of biofilms and pre-formed biofilms suggests its potential as a therapeutic agent for infections caused by biofilm-forming S. epidermidis resistant to conventional treatments.